FERMENTASI LIMBAH NYPA FRUTICANS WURMB UNTUK ANALISA KANDUNGAN EtOH DALAM BIOETANOL DAN GASOHOL E-10 DENGAN GC - Rochyani, Neny; Oktaviani, Santy; Anggraini, Reni Afni (JURNAL MEDIA TEKNIK, 2011)
ABSTRACT Bioethanol is EtOH that is made from nabaty material through fermentation process. This bioethanol is used as the substitution material on the gasoline, which is known as gasohol. It’s analysis purpose to know the EtOH content inbioethanol which is from Nypa fruticans wurmbwaste with 48, 72, 96 hours fermentation and gasohol E-10. The result that is got from the analysis is that the EtOH content (% volume) that has standard specification minimum 99,5 (beforedenaturation) got on bioethanol sample with 72 hours fermentation is 99,56, while the EtOH content for 48 hours is 97,41 and 96 hours is 99,03 so they have not fulfilled established standard specification. To gasohol E-10 sample has fulfilled the standard specification minimum 94 % volume and the result of value is 95,2 % volume.Keywords : Bioethanol, Nypa fruticans wurmb, Gasohol E-10